Torsades de Pointes in Patients with Polymyalgia Rheumatica - Lazzerini, Pietro E.; Bertolozzi, Iacopo; Acampa, Maurizio; Fulceri, Rosella; Laghi-Pasini, Franco; Capecchi, Pier Leopoldo (Current Pharmaceutical Design, 2018)
Polymyalgia rheumatica (PMR) represents the most common inflammatory rheumatic disease of the elderly. It is characterized by synovitis of proximal joints and extra-articular synovial structures, along with chronic high-grade systemic inflammation. PMR is closely related to giant cell arteritis (GCA), a large–vessel vasculitis that involves the major branches of the aorta, particularly the extracranial branches of carotid artery including temporal arteries. It is currently believed that PMR and GCA may represent different manifestations of the same disease process. Chronic systemic inflammation is presently recognized as one of the key pathogenic mechanisms underlying cardiovascular disease and associated complications, including cardiac arrhythmias and sudden death. In this regard, several studies demonstrated that besides promoting structural heart disease, inflammatory activation may also be per se arrhythmogenic, via cytokine-mediated effects on cardiac electrophysiology. In particular, increasing evidence points to inflammation as a novel risk factor for QTc prolongation and related life-threatening arrhythmias, specifically Torsade de Pointes (TdP). Starting from the report of two cases of TdP occurring in PMR patients with active disease and elevated circulating IL-6 levels, we here reviewed literature data regarding heart involvement and arrhythmic events in PMR/GCA, as well as TdP risk in inflammatory diseases. Potential underlying mechanisms were dissected, by focusing on the driving role of inflammatory activation.
Keywords: cardiovascular disease